2017
DOI: 10.1177/0306396816685030
|View full text |Cite
|
Sign up to set email alerts
|

Framing Ferguson: Fox News and the construction of US racism

Abstract: In August 2014, police officer Darren Wilson shot unarmed Michael Brown, sparking months of protests in Ferguson, Missouri and other American cities and capturing worldwide media attention. This article presents a critical discourse analysis of Fox News Channel’s segments from August 2014 to March 2015. It systematically uncovers themes and larger discourses within five major areas: blaming black victims in the characterisation of Michael Brown and his shooting death, blaming black leaders, blaming the black c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 13 publications
1
23
0
Order By: Relevance
“…Consistent with our expectations, results show a consistent effect of criminal history. As described above, research has consistently shown that media reports of police violence often use an unrelated criminal history in order to paint a citizen as a potential threat to a police officer (Hirschfield and Simon ; Mills ; Ray et al. ; Room ; Stone and Socia ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Consistent with our expectations, results show a consistent effect of criminal history. As described above, research has consistently shown that media reports of police violence often use an unrelated criminal history in order to paint a citizen as a potential threat to a police officer (Hirschfield and Simon ; Mills ; Ray et al. ; Room ; Stone and Socia ).…”
Section: Discussionmentioning
confidence: 99%
“…() show conservative Twitter users commenting on the Michael Brown incident frequently posted messages that portrayed Brown as a dangerous threat, including images that literally portrayed Brown as a hulking, violent monster based on his alleged involvement in a robbery prior to his shooting. Additional research shows that Fox News portrayals of the Ferguson shooting similarly followed these trends of both relying on official reports and police testimony to frame the incident and using hyperbolic language to describe the size differential between Brown and Wilson (Mills ). These references to the unrelated criminal histories, often irrelevant to the incident, may temper public sympathy for citizens while simultaneously validating the fears reported by engaging officers by playing on the general social stigma faced by individuals with criminal backgrounds (Wakefield and Uggen ).…”
Section: Background and Literature Reviewmentioning
confidence: 94%
See 2 more Smart Citations
“…Utilizing St. Louis as a sort of Midwestern mecca, white supremacists and neo-Nazis often collaborate and then fan out into the rural areas to implement discriminatory practices. Mills (2017) notes that for many black citizens of Missouri, especially within the St.…”
Section: University Of Missouri and The Racial Dividementioning
confidence: 99%